1)0,4у-6=12 2)х+6=5+4х 3)13-3(х+1)=4-5х 4)0,2(3х-5)-0,3(х-1)=-0,7 5)1,2(5-4х)=-6(0,8х+1)

1)0,4у-6=12 2)х+6=5+4х 3)13-3(х+1)=4-5х 4)0,2(3х-5)-0,3(х-1)=-0,7 5)1,2(5-4х)=-6(0,8х+1)
Гость
Ответ(ы) на вопрос:
Гость
0.4у-6=12 0.4у=6+12 0.4у=18 У=18:0.4 У=45 2) х+6=5+4х 6-5=4х-х 1=3х 3х=1 х=1:3 3)13-3(х+1)=4-5х 13-3*х-3*1 13-3х-3=4-5х 13-3-4=3х-5х 6=-2х 2х=-6 Х=-6:2 Х=-3 4)0,2(3х-5)-0,3(х-1)=-0,7 0,2*3х-0,2*5-0,3*х-0,3*(-1)=-0.7 0,6х-1-0,3х+0,3=-0,7 0,6х-0,3х=1-0,3-0,7 0,3х=0 Х=0 5)1,2(5-4х)=-6(0,8х+1) 1,2*5-1,2*4х=-6*0.8х-6*1 6-4,8х=-4,8х-6 4,8х-4,8х=-6-6 0х=-12 х=не возможно
Не нашли ответ?
Ответить на вопрос
Похожие вопросы